Prevalence of rapid weight loss in Olympic style wrestlers. Issue 1 (31st December 2022) - Roklicer, Roberto; Rossi, Carlo; Bianco, Antonino; Stajer, Valdemar; Ranisavljev, Marijana; Todorovic, Nikola; Manojlovic, Marko; Gilic, Barbara; Trivic, Tatjana; Drid, Patrik
ABSTRACT: Background: The methodology applied for rapid weight loss (RWL) among elite wrestlers is quite unexplored. Therefore, the aim of this study was to analyze the prevalence of sources of influence and methods used for RWL and to determine the differences between wrestling styles. Methods: A total of 229 wrestlers who competed at the World Championship held in Belgrade, Serbia, participated in this research. All respondents completed a questionnaire designed to evaluate RWL patterns in combat athletes. Participants were classified according to wrestling style: Greco-Roman, freestyle, and women wrestling. Results: Sixty-nine percent of wrestlers had previously lost weight to compete. Most respondents start losing weight approximately seven days before a competition. Athletes reported that they commonly reduced 3.84 ± 2.82 kg to reach the target weight. The wrestling coach represents the most influential person in terms of RWL strategies, while nutritionists and physicians have the least impact on the weight-cutting process. Regarding the methods applied, differences between all the three styles were found in the following variables: training in a heated room, restricting fluid ingestion, training in plastic suits, gradual dieting, increased exercise, diet pills, and sauna. The most frequently used techniques were increased exercise, gradual dieting, training in a heated room, and sauna for all competitors. Diet pills, diuretics, laxatives, and vomiting were the least implemented methods. Conclusions: The obtained results suggest that most wrestlers practice RWL despite the harmful health effects. The education of wrestling coaches is necessary in order to control and decrease the negative impact of RWL.